Wednesday, March 6, 2013

Công thức đạo hàm

Dưới đây là các công thức đạo hàm cần nhớ ( u = u(x))

$$
 \begin{array}{l}
 (x^{\alpha})' = \alpha x^{\alpha - 1} \qquad (u^{\alpha})' = \alpha u^{\alpha - 1}u' \\ \\

(\sqrt{x})' = \frac{1}{2\sqrt{x}} \qquad (\sqrt{u})' = \frac{u'}{2\sqrt{u}} \\ \\

(\frac{1}{x})' = -\frac{1}{x^{2}} \qquad (\frac{1}{u})' = -\frac{u'}{u^{2}} \\ \\

(sinx)' = cosx \qquad (sinu)' = u'cosu \\ \\

(cosx)' = -sinx \qquad (cosu)'=-u'sinu \\ \\

(tanx)' = \frac{1}{cos^{2}x} \qquad (tanu)' = \frac{u'}{cos^{2}u} \\ \\

(cotx)' = -\frac{1}{sin^{2}x} \qquad (cotu)' = \frac{u'}{sin^{2}u} \\ \\

(e^{x})' = e^{x} \qquad  (e^{u})' = u'e^{u} \\ \\

(a^{x})' = a^{x}lna \qquad  (a^{u})' = u'a^{u}lna \\ \\

(lnx)' =\frac{1}{x} \qquad  (lnu)' =\frac{u'}{u} \\ \\

(log_{a}x)' = \frac{1}{xlna} \qquad (log_{a}u)' = \frac{u'}{ulna}

\end{array}
$$

No comments:

Post a Comment

Các bài đã đăng